The Effect of in Vitro Modified Basic Media Types on the Morphological Growth of Dendrobium anosmum Lindl. Mutant Orchids Resulting from Gamma Ray Irradiation (Agrotrop : Journal on Agriculture Science, 2026)
The demand for orchid seedlings continues to increase every year, resulting in significant price fluctuations. To meet market demand, a method for rapid plant propagation is needed. The solution is to multiply plants through in vitro culture. The choice of growth media in in vitro culture is a crucial factor; Therefore, the media used must have sufficient nutrients for plant growth. This study aims to determine the effect of in vitro modified basic media types on the morphological growth of Dendrobium anosmum Lindl. mutant orchids resulting from gamma ray irradiation. This study was conducted at the Tissue Culture Laboratory, Faculty of Agriculture, Udayana University, from January to April 2025, using a Completely Randomized Split Plot Factorial Design and 8 replications. The first factor was the type of gamma-ray irradiation mutant dose and the second factor was the type of in vitro modified base medium. The results showed a significant interaction between the gamma-ray irradiation dose and the type of in vitro modified base medium on the observed variable of plantlet height, but no interaction was observed for the other research variables. The type of modified FFM base medium produced the highest value for each type of D. anosmum mutant.
Keywords: Basic Media; D. anosmum Lindl.; Gamma Ray Irradiation; In Vitro Culture